Developing Singakerta Village Through the Establishment Sekaa Gong | Membangun Desa Singakerta Melalui Pembentukan Sekaa Gong - I Komang Werdi Darmawan; Hendra Santosa (Pusat Penerbitan LPPMPP ISI Denpasar, 2024)
The Thematic Community Service Program Developing Village was conducted in Singakerta Village, focusing on Banjar Tunon. The first activity was to observe the track record of the Karawitan in Singakerta Village. From the case study, a generation-related problem was found. The non-developing potential of the Childern’s Traditional Music Group was formed in 2013, so researchers intend to rebuild the Childern’s Traditional Music Group to become a work program in the Thematic Community Service Program Developing Village. The name of Childern’s Traditional Music Group is Jenggala Kauripan. The research method applied is a qualitative method with the process of collecting data through observation and interviews. The rehearsal at Jenggala Kauripan Childern’s Traditional Music Group is held four times a week by applying the Balinese Karawitan teaching method, namely the Catur Maguru method such as maguru lima, maguru panggul, maguru kuping, and maguru rasa and also accompanied by additional procedures, such as the drill method and the questioning method. Through this training, the results have been staged two times so that the contribution of this training can be achieved.